Hubungan Beban Kerja Fisik dan Sikap Kerja dengan Unsafe Action pada Pekerja Bagian Tab PT. Solo Murni Boyolali - Sofi Nur Jannah; Hengky Ditya Eko Nugroho; Ratna Fajariani (Journal of Applied Agriculture, Health, and Technology, 2023)
The rapid development of the industry, besides its positive impact, also gives rise to various problems such as the increased risk of occupational accidents in the workplace. The cause of a work accident is an unsafe act in the form of human error. Up to 88% of workplace accidents are caused by unsafe actions. Personal factors are factors that influence the formation of dangerous actions. The physical workload is related to the physical capacity of the worker, the higher the workload that the worker receives, the more fatigue will be created, thereby reducing concentration at work, easy dangerous behavior occurs. Work attitude is the single most important factor in determining workplace safety. In this study, the sampling technique used is intentional sampling with a total of 70 respondents. Physical workload was measured by pulseoximeter, work attitude and unsafe actions were measured by questionnaire. Two-variable analysis used Somers test while multivariate analysis used ordinal logistic regression analysis. Statistical test results show that the physical workload variable has a p = 0.000 (<0.05) value and the work attitude variable has a p = 0.002 (< 0.05) value. Based on the ordinal logistic regression test, the physical workload variable is known to have a greater influence on hazardous actions with a Wald value of 20,383.